PKM Kelompok Usaha Diversifikasi Lowe Sebagai Upaya Peningkatan Pendapatan di Desa Tongkonunuk Kecamatan Pagimana Kabupaten Banggai Provinsi Sulawesi Tengah - Ramadhani Chaniago; Wahyudi Hasan (Al-Khidmah, 2018)
Tongkonunuk Village is one of the producers of lowe banana which is a local potential in Banggai Regency. The village is 65 km from the city of Luwuk which is the capital of Banggai Regency, is a center of lowe banana production ranging from 1.3 tons per planting season with a harvest period every 3-4 months. With its natural conditions consisting of 60% plains, 25% hills and 15% mountains which are very potential for food crop cultivation or plantation crops, for example corn, cassava, rice paddy, field rice and lowe banana commodities typical of the Banggai Regency. The objectives of this program are: (1) Availability of equipment that is needed by the community to diversify lowe products; (2) Training and practice of diversifying lowe products, (3) Producing packaging designs to attract consumers, (4) Realizing a professional organizational structure, (4) Establishing a partnership pattern with the Banggai District Cooperatives and SMEs Office, as well as healthy and empowered group management and reliable business bookkeeping.